1988
DOI: 10.1042/bj2560251
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant action of taurine, hypotaurine and their metabolic precursors

Abstract: It has been suggested that taurine, hypotaurine and their metabolic precursors (cysteic acid, cysteamine and cysteinesulphinic acid) might act as antioxidants in vivo. The rates of their reactions with the biologically important oxidants hydroxyl radical (.OH), superoxide radical (O2.-), hydrogen peroxide (H2O2) and hypochlorous acid (HOCl) were studied. Their ability to inhibit iron-ion-dependent formation of .OH from H2O2 by chelating iron ions was also tested. Taurine does not react rapidly with O2.-, H2O2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
240
1
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(251 citation statements)
references
References 28 publications
8
240
1
2
Order By: Relevance
“…Therefore, a molecule can inhibit the reactions by quenching ROSs. Although several studies (Cozzi et al 1995;Redmond et al 1996) reported that taurine scavenges ROSs, this finding has not been supported by several other groups (Aruoma et al 1988;Shi et al 1997). Taurine is known to be a powerful scavenger of hypochlorous acid (HOCl) (Thomas et al 1986).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, a molecule can inhibit the reactions by quenching ROSs. Although several studies (Cozzi et al 1995;Redmond et al 1996) reported that taurine scavenges ROSs, this finding has not been supported by several other groups (Aruoma et al 1988;Shi et al 1997). Taurine is known to be a powerful scavenger of hypochlorous acid (HOCl) (Thomas et al 1986).…”
Section: Discussionmentioning
confidence: 83%
“…The following mechanisms have been proposed for the antioxidant effects of taurine: (1) As a direct antioxidant, taurine would quench and detoxify some reactive intermediates such as hypochlorous acid generated by myeloperoxidase (Wright et al 1986;Huxtable 1992;Timbrell et al 1995), nitric oxide (Redmond et al 1996), and H 2 O 2 (Cozzi et al 1995). Taurine was also reported to have scavenged HO • , but this scavenging activity has been shown to be weak compared to that of glucose and mannitol (Aruoma et al 1988). (2) As an indirect antioxidant, taurine may protect cells via intercalating into the membrane and stabilizing it (Nakashima et al 1982;Gordon et al 1992;Timbrell et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that CP toxicity is associated with oxidative cell damage [27]; thus, therapeutic strategies aim to limit free radical-mediated urinary bladder injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…Of all solutes accumulated at relatively high concentrations in some situations, hypotaurine, with its reactive sulfur atom ( Fig.·2), is one of the strongest antioxidants, able to scavenge OH radicals (which bond to the sulfur atom, converting hypotaurine into taurine) as well as HOCl (Aruoma et al, 1988). Hypotaurine is known to occur at osmotically P. H. Yancey 2822 significant levels in two situations: mammalian reproductive fluids (where it appears to act as an osmolyte and may protect sperm and eggs from oxygen radicals; Setchell et al, 1993) and marine animals living in sulfide-laden waters (see Sulfide detoxification, below).…”
Section: Antioxidationmentioning
confidence: 99%